Web-Based Application Development for Training Data Management Using REACTJS - Hany Juliana Saragih Sitio; Irene Christovita; Rahma Kamila Ahmad; Yanto Setiawan (Indonesian Journal of Multidisciplinary Science, 2023)
This research was conducted to develop a web-based information system for training data management to improve training programs and business opportunities for companies. The management of training data includes training programs, participant data, invoice data, attendance numbers of participants, certificates and reports that have not been optimally carried out by the company. Based on these problems, the training manager was less effective and efficient. From these problems, this research is aimed at developing a system managing training data. The method used is scrum method. Web-based application design using ReactJS and MySQL as the database, with the Java and JavaScript programming languages. The development of this web-based information system aims to make it easier to manage training data that has been implemented according to the schedule and timeline of the training program. From the results of system integration test (SIT) and user acceptance test (UAT) it can be concluded that information systems developed with the addition of other features increase effectiveness by as much as 90.4%, efficiency is obtained by as much as 91.2%, then for user satisfaction by employees and admin as much as 92.6%. The evaluation results that have been carried out by the application are very feasible to use, namely 91.5%.